A model of strategic-adaptive financial planning for military units of the Armed Forces of Ukraine: an analytical and applied approach - Tsiukalo, Liudmyla; Panukhnyk, Olena; Ostapchuk, Tetiana; Syzov, Alim; Dyachenko, Serhiy (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
Background. Under the current conditions of full-scale military invasion, the issue of rational financial resource management within the defense sector has become exceptionally relevant and critically important for ensuring the state′s defense capability, sustaining military operations, and maintaining overall national security resilience. In this context, the mechanism for returning a share of personal income tax (PIT) revenues to the military units of the AFU acts as a financial catalyst for enhancing it′s capability and as an instrument for reinforcing the economic autonomy of defense institutions. At the same time, research indicates that the existing approach to utilizing the returned funds requires a higher degree of adaptability. Therefore, the necessity to develop a model of strategic-adaptive financial planning for military units has occurred, one that integrats mathematical modeling, weighted ranking, scenario forecasting, and inflation adjustment tools. The study’s objective is to conceptualize, develop, and test a strategic-adaptive financial planning model for military units, based on the partial PIT return mechanism, as a tool to enhance the quality and operational speed of managerial decisions made by AFU unit commands. Methods. The article proposes and validates an original methodology for strategic-adaptive financial planning for military units, based on methodological approach combining mathematical modeling; a weighted ranking system for needs assessment; prioritization of expenditure areas; scenario forecasting across three probable operational tragectories of combat developments (baseline, escalation, and de-escalation), taking into account the inflation index; weekly and quarterly expenditure profiling; and pilot testing of the model using the examples of a separate mechanized brigade and a communications brigade. Results. The testing of the methodology using simulated cases demonstrates substantial differences in the financial capabilities among various military units: at the initial level of PIT-based return, a separate mechanized brigade may receive approximately 6, 480, 000 UAH per month, whereas a communications brigade would receive significantly less – around 410, 400 UAH per month. The proposed model enables flexible and prompt reallocation of resources according to the selected scenario ("A", "B", or "C"). The integration of the inflation index allows quarterly plan adjustments and reduces the risk of financial shortfalls. The scientific research novelty lies in formulating an original methodological approach and an algorithm for adaptive financial planning for military units based on the partial PIT return mechanism, which integrates scenario forecasting, weighted ranking, and inflationary adjustment. Conclusion. The validated strategic-adaptive financial planning methodology provides military units of the AFU with a tool for strengthening financial autonomy and ensuring the efficient use of funds originated from the return of 10 % of PIT revenues. The anticipated effect of implementing the model includes reducing the risks of misallocation of financial resources, increasing transparency in budgetary decisions, and enhancing the financial sustainability of military units under wartime conditions.